Transinguinal Ultrasound versus Magnetic Resonance in Spica Cast after Closed Reduction of Unstable Hips in DDH - Nicola Guindani; Federico Chiodini; Maurizio De Pellegrin (MDPI AG, 2024)
Background. During the treatment of unstable hips in developmental hip dysplasia (DDH), the position of the femoral head must be assessed in spica cast (SC) after reduction. A transinguinal sonographic technique (TIT) to the hip joint has been previously described in the literature. The aim of this study is to evaluate the agreement among TIT and MR to identify hip reduction. Methods. From 2016 to 2019, 14 consecutive newborns (10 female, 4 males) with a mean age of 2.97 ± 1.29 months were treated with closed reduction in SC. A total of 4/14 children had bilateral unstable DDH. Out of 18 hips, there were 8 hips type IV and 10 hips type IIIA, according to Graf. SC were changed monthly and hips were checked both with TIT and MR, looking for persistent dislocation. Results. Overall, a mean of 2.61 SC/hip (mode = 3) was accomplished, accounting for 47 procedures, with 46 reduced hips and 1 dislocated hip: TIT and MR always agreed on the same result (47/47; Cohen k = 1, CI95 1.00 to 1.00). Conclusions. The inguinal ultrasound technique described by van Douveren showed perfect agreement with MR and might be considered a reliable alternative to check the position of the femoral head during the conservative treatment of hip dysplasia in spica cast.